GRAMMATICAL AND LEXICAL COHESION IN ED SHEERANS’ SONG LYRICS IN THE “PLUS” ALBUM - Tetema Telaumbanua (Jurnal Education and Development, 2021)
This research aimed at analyzing the grammatical and lexical cohesion in Ed Sheerans’ song lyrics in the ‘Plus’ Album. The kind of this research is qualitative research with descriptive approach. Reseacher used the Halliday and Hasan’s grammatical and lexical cohesion theory to analyze the grammatical and lexical cohesion in this song. The result of this research showed that there were four grammatical cohesion categories found they are reference, substitution, ellipsis, and conjunction, and two lexical cohesion categories found they are reiteration and collocation. The data of this research were words, phrases, and sentences. Grammatical and lexical cohesion creates relationships among the elements in the lyrics. Therefore, the existence of both grammatical and lexical cohesion enhances cohesiveness in the lyrics. Based on summary of the result, that grammatical cohesion is more dominated in the lyrics of the song more than lexical cohesion. In grammatical cohesion, reference consisted of 556 times found in the lyrics of the song, and conjunction consisted of 79 times found in the lyrics of the song. While in lexical cohesion, reiteration consisted of 98 times found in the lyrics and collocation consisted of 7 times found in the lyrics of the song. It is suggested that English learners should pay attention about the usage of grammatical and lexical cohesion in order to be able to produce a good discourse. For the teachers, hopefully this research could be used to enrich their teaching material.